Bonding properties and mechanism of the interface between precast UHPC and post-cast UHPC. (September 2022) - Ding, Jingnan; Zhu, Jinsong; Kang, Jingfu
Abstract: In the application of UHPC joints between the precast UHPC segmental bridges, the bonding behavior of UHPC-to-UHPC interface can influence the overall integrity and the performance of the structures. The current study used the direct shear test, splitting tensile test and slant shear test to clarify the bonding properties and mechanism of the interface between precast UHPC and post-cast UHPC. The different surface preparations, including as-cast, chiseled and grooved, were considered and discussed. DIC technique was employed to observe the failure process of UHPC bond specimens. The cohesion coefficient and friction coefficient were recommended by data analysis. The results demonstrated that the UHPC bond specimens presented adhesive failure along the bonding interface without any failure was observed in the precast UHPC or post-cast UHPC. The surface preparation showed various effects on the bond strength of interface under different stress states. The bond strength of the interface is ranked from lowest to highest as follows: as-cast interface, chiseled interface and grooved interface. The interface shear bond strength increased little with chiseled preparation, but the tensile bond strength increased significantly. The interface with grooved preparation showed a greater improvement in shear bond strength than in tensile bond strength. The correlations between the interface bond strength and chemical bonding force, Van der Waals force, mechanical interlocking force and the bridge effect and dowel action of steel fibers were discussed. The values of cohesion coefficient were 0.983 MPa, 0.995 MPa and 11.818 MPa for as-cast interface, chiseled interface and grooved interface, respectively. The corresponding friction coefficient for each surface preparation was 1.065, 1.126 and 1.190, respectively.